2000
DOI: 10.2136/sssaj2000.643873x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Characterization of Humic Substances by Solid‐State Carbon‐13 Nuclear Magnetic Resonance

Abstract: The compositions of humic acids (HAs) from various Histosols in North America and Europe, of similarly treated plant‐extracted materials (PEMs), of coal‐extracted humic acids, and of International Humic Substances Society (IHSS) Florida peat were quantified by solid‐state 13C nuclear magnetic resonance (NMR). In order to obtain quantitative intensities, the peak areas in direct‐polarization 13‐kHz magic‐angle spinning (DPMAS) 13C NMR spectra were corrected for incomplete relaxation by factors measured in cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
254
1
3

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 296 publications
(275 citation statements)
references
References 41 publications
17
254
1
3
Order By: Relevance
“…The 90°pulse length was 4 μs. The recycle delay was 40 s for Hatahara and 26 s for Lago Grande, which is >4 times the measured spin−lattice relaxation time 23,24 (see also Figure S2 in the Supporting Information). A spectrum with 100-s recycle delay experiments confirmed complete relaxation, as did >95% observability in spin counting analysis.…”
Section: ■ Materials and Methodsmentioning
confidence: 78%
“…The 90°pulse length was 4 μs. The recycle delay was 40 s for Hatahara and 26 s for Lago Grande, which is >4 times the measured spin−lattice relaxation time 23,24 (see also Figure S2 in the Supporting Information). A spectrum with 100-s recycle delay experiments confirmed complete relaxation, as did >95% observability in spin counting analysis.…”
Section: ■ Materials and Methodsmentioning
confidence: 78%
“…Mao et al (2002) reported that the sp 2 carbons (110-220 ppm) or -COOH tend to be underrepresented by CP MAS 13 C NMR due to their longer relaxation times (T 1 , spin-lattice relaxation time). According to this observation, -COOH of the lipid may be in rigid domains, corresponding to longer T 1 Mao et al, 2000). When lipid was coated on char, a small peak at 167 ppm (-COOH) appeared and even more intensive with increasing coated lipid, indicating that some rigid domains changed to more mobile domains, corresponding to the reduced T 1 of 13 COOH.…”
Section: Tablementioning
confidence: 82%
“…The purpose is not to repeat what is available elsewhere, such as reviews of applications, noted previously, or basic theory and factors affecting quantitative reliability of NMR spectra (Preston et al 1984;Axelson 1985;Wilson 1987Wilson , 1991Fründ et al 1994a, b;Kinchesh et al 1995;Conte et al 1997a, b;Veeman 1997;Oades 1999, 2000a, b;Hu et al 2000;Mao et al 2000). The second purpose is to raise awareness of the need to develop NMR infrastructure and expertise in SOM studies in a variety of contexts.…”
mentioning
confidence: 99%